C reactive protein and depressive symptoms in hemodialysis patients: A questionable association. Issue 4 (27th September 2016) - Chilcot, Joseph; Friedli, Karin; Guirguis, Ayman; Wellsted, David; Farrington, Ken; Davenport, Andrew
Abstract: Introduction: Patients with advanced chronic kidney disease (CKD) on haemodialysis (HD) may have increased C reactive protein (CRP) values and depressive symptoms. There is debate about the strength and nature of previously reported associations. We investigated these issues in a cohort of patients on HD. Methods: We screened for depressive symptoms using two valadiated depression screening tools: the Beck Depression Inventory‐II (BDI‐II), Patient Health Questionnaire (PHQ‐9). Demographic and clinical correlates of depression symptoms were eveluated in adjusted linear and logistic regression models, which included extra renal comorbidity and high CRP (>5 mg/L). Findings: Three hundred and ninety‐six HD patients were studied; 63.1% male, mean age 63.1 ± 16.4 years, median CRP 6 (5–15) mg/L. Depression scores were similar in those with normal and high CRP (BDI‐II (9(5–17) vs. 11(6–20)) or PHQ (4(2–9) vs. 6(2–10)). In adjusted multivariable regression BDI‐II scores were associated with previous history of depression (β 10.8, P < 0.001), serum albumin (β 0.41, P < 0.001), anuria (β 2.4, P < 0.037), diabetes (β 2.7, P = 0.033), and age (β −0.10, P = 0.009). High CRP was not independently associated with BDI‐II (β 2.20, P = 0.057), though was with PHQ‐9 (β 1.20, P = 0.046). In logistic regression those with high CRP were 1.9 times more likely to score ≥16 on BDI‐II screening (P = 0.016), but did not relate significantly to a PHQ‐score ≥10. Discussion: A relationship was observed between CRP and depression symptoms, though the effect was small, of unlikely clinical significance, and inconsistent between depression measures. Previous reports of this association may reflect overlap between symptoms of depression and advanced CKD.